Redifinisi Agama - Fibry Jati Nugroho (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2017)
Definition of prevailing religion in general (world religions) have been constructed in such a manner in accordance with the concept of rulers. Before the import of religion comes, the local belief has gained a place and has fostered human society into a "religion". However, the politicization of religion entrants positioned local beliefs become the enemy in his hometown. Starting with the framing of the occult, mystical, syncretic, tahkyul and others. Minority belief started alienated in a hometown. In the eyes of the sociology of religion, Durkheim gives the sense that religion is sui generis in a society. Religion is a system of beliefs and practices that have united and are associated with things that are sacred / holy, beliefs, and practices which unite into one single moral community. Therefore, it should be underlined the roots of religious contestation world paradigm here is uniformity of definition of religion.